PENERAPAN MEDIA KARTU BILANGAN PADA PEMBELAJARAN MATEMATIKA SISWA KELAS II SD NEGERI 4 MEGANG SAKTI - Tika Avrianti; Elya Rosalina; Aswarliansyah Aswarliansyah (LP4MK STKIP PGRI Lubuklinggau, 2021)
The research objective was to determine the completeness of learning outcomes in the application of number card media in mathematics learning for grade II students of SD Negeri 4 Megang Sakti. This research method uses an experimental research method with a quasi-experimental design with the categories of pre-test and post-test group. The subjects of this study were 11 grade students of SD Negeri 4 Megang Sakti. The data collection technique uses a test technique in the form of 6 essay questions. The data were analyzed using the